PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA, DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN (Studi kasus pada Karyawan Departemen Produksi Sub Bagian Lapangan Samberah di PT. Pertamina Hulu Sanga-Sanga) - AL AFGANI, DJERIL; JOHANSYAH, JOHANSYAH; PUTRI, EVA NOORHYA AKHMAR RAMADHAN (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2021)
PT. Pertamina Hulu Sanga-Sanga has a working principle that refers to Pertamina's 3 golden rules (PIP), namely 1. You and I Comply with laws, policies, regulations and procedures. 2. You and I must immediately intervene in unsafe actions and violate the rules. 3. You and I Care about everyone and the environment around us. With these principles encourage the development of agencies to the current state, but in its development, the level of stability of employees bring back consequences to the culture itself, thus affecting the performance of its employees. This study aims to determine the effect of Leadership Style, Work Environment, and Work Culture on Employee Performance in the Samberah Field Subdivision at PT. Pertamina Hulu Sanga-Sanga. The population of this study was 41 employees and all were sampled based on the total sample method or census. This study uses multiple linear regression analysis methods. The questionnaire instrument was used as a data collector. The analysis results obtained leadership style and work environment have a positive and significant effect on employee performance in the Samberah Field Subdivision at PT. Pertamina Hulu Sanga-Sanga . Work culture has a positive effect but does not significantly influence employee performance in the Samberah Field Subdivision at PT. Pertamina Hulu Sanga-Sanga. Leadership style, work environment, and work culture simultaneously influence the improvement of employee performance in the Samberah Field Subdivision at PT. Pertamina Hulu Sanga-SangaKeywords: leadership style, work environment, work culture, performance.